Circulating S100 proteins effectively discriminate SLE patients from healthy controls: a cross-sectional study - Šumová, Barbora; Cerezo, Lucie Andrés; Szczuková, Lenka; Nekvindová, Lucie; Uher, Michal; Hulejová, Hana; Moravcová, Radka; Grigorian, Mariam; Pavelka, Karel; Vencovský, Jiří; Šenolt, Ladislav; Závada, Jakub (Rheumatology international, 2019)
S100 proteins are currently being investigated as potential diagnostic and prognostic biomarkers of several cancers and inflammatory diseases. The aims of this study were to analyse the plasma levels of S100A4, S100A8/9 and S100A12 in patients with incomplete systemic lupus erythematosus (iSLE), in patients with established SLE and in healthy controls (HCs) and to investigate the potential utility of the S100 proteins as diagnostic or activity-specific biomarkers in SLE. Plasma levels were measured by ELISA in a cross-sectional cohort study of 44 patients with SLE, 8 patients with iSLE and 43 HCs. Disease activity was assessed using the SLEDAI-2K. The mean levels of all S100 proteins were significantly higher in SLE patients compared to HCs. In iSLE patients, the levels of S100A4 and S100A12 but not S100A8/9 were also significantly higher compared to HCs. There were no significant differences in S100 levels between the iSLE and SLE patients. Plasma S100 proteins levels effectively discriminated between SLE patients and HCs. The area under the curve (AUC) for S100A4, S100A8/9 and S100A12 plasma levels was 0.989 (95% CI 0.976-1.000), 0.678 (95% CI 0.563-0.792) and 0.807 (95% CI 0.715-0.899), respectively. S100 levels did not differentiate between patients with high and low disease activity. Only the S100A12 levels were significantly associated with SLEDAI-2K and with cSLEDAI-2K. S100 proteins were significantly higher in SLE patients compared HCs and particularly S100A4 could be proposed as a potential diagnostic biomarker for SLE.
Keywords: protein S100A12; Cross-Sectional Studies; Calgranulin A; Male; S100A12 Protein; Middle Aged; mužské pohlaví; S100 Calcium-Binding Protein A4; studie případů a kontrol; kalgranulin B; průřezové studie; mladý dospělý; Adult; systémový lupus erythematodes; S100 proteins; proteiny S100; Young Adult; ženské pohlaví; Humans; kalgranulin A; S100 Proteins; Disease activity; Calgranulin B; Lupus Erythematosus, Systemic; lidé středního věku; dospělí; SLE; Biomarkers; Female; S100 kalcium vázající protein A4; lidé; Case-Control Studies